2019
DOI: 10.1038/s41422-019-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning up stalled ribosome-translocon complexes with ufmylation

Abstract: Ufmylation, a metazoan-specific ubiquitin-like post-translational modification, is implicated in numerous cellular processes and mammalian phenotypes. Here, Wang et al. uncover an important function of ribosome ufmylation in protein quality control at ribosomes that have stalled during co-translational translocation of endoplasmic reticulum (ER)-targeted proteins. Post-translational modifications (PTMs) diversify the proteome and modulate protein function on faster time scales compared to transcriptional or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 10 publications
3
47
0
Order By: Relevance
“…Currently, there are multiple ongoing clinical trials worldwide to assess the effectiveness and safety of certain drugs such as chloroquine, arbidol, remdesivir, and favipiravir [ 22 ]. In vitro data has suggested that chloroquine inhibits virus replication [ 23 ], although clinical testing has failed to provide such a strong case so far. Also, clinical studies suggest the apparent efficacy of chloroquine phosphate in the treatment of pneumonia following COVID-19 infection [ 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…Currently, there are multiple ongoing clinical trials worldwide to assess the effectiveness and safety of certain drugs such as chloroquine, arbidol, remdesivir, and favipiravir [ 22 ]. In vitro data has suggested that chloroquine inhibits virus replication [ 23 ], although clinical testing has failed to provide such a strong case so far. Also, clinical studies suggest the apparent efficacy of chloroquine phosphate in the treatment of pneumonia following COVID-19 infection [ 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…ACE2 expression was mainly observed in enterocytes, renal tubules, gallbladder, cardiomyocytes, male reproductive cells, placental trophoblasts, ductal cells, eyes, and vasculature. Another study showed that ACE2 expression was increased with age in the pulmonary alveolar epithelial barrier, cardiomyocytes, and vascular endothelial cells, which may explain age-linked susceptibility to SARS-CoV-2 [ 25 ].…”
Section: Pathogenesis Of Sars-cov-2mentioning
confidence: 99%
“…As of the time of writing this manuscript, there are no clinically effective anti-viral drugs against coronaviruses, like SARS-CoV and MERS-CoV [ 12 ]. Anti-viral medications like Remdesivir can stop the virus from replicating, halting the disease state from in vitro and in animal models [ 13 ]. Even though the FDA had conditionally approved its use in selective situations, the therapeutic potential of Remdesivir is still controversial and warrants further investigation [ [14] , [15] , [16] ].…”
Section: Covid-19 Pandemic and Anti-viral Challengesmentioning
confidence: 99%